2021
DOI: 10.1097/scs.0000000000007836
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin for a Better Scar in Cleft Lip Surgery: A Prospective Randomized Control Trial

Abstract: Introduction: An unsightly scar following cleft repair can undo the good work of even an experienced surgeon. A functioning orbicularis oris muscle beneath the lip scar maintains a zone of dynamic tension resulting in a stretched scar. Botulinum toxin type A (BTA) can be used to create a temporary paralysis of the orbicularis muscle during the healing phase. This may lead to better scar formation after a cleft lip repair. Method: The present prospective randomized control trial enrolled 28 infants with unilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Table 1 summarizes the study characteristics that were included. Four randomized controlled trials (RCTs) were conducted in China, Mexico, and India, with a total of 161 randomized patients 15–18 . The researchers compared 83 scars treated with BTXA to 78 scars treated with a placebo.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 summarizes the study characteristics that were included. Four randomized controlled trials (RCTs) were conducted in China, Mexico, and India, with a total of 161 randomized patients 15–18 . The researchers compared 83 scars treated with BTXA to 78 scars treated with a placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Although BTXA into the underlying dermis could also diffuse into the muscular layer, 4 trials injected BTXA into the subjacent orbicularis oris muscle instead of subcutaneous injection. In addition, Sonane et al 18 showed that there was no statistically significant difference between infants with cleft lip alone or with a cleft of lip and palate on VAS, VSS, and scar width.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations